P2P islamic fintech investment innovation : a proposal of mushārakah smart contract model for SMES financing and social - Adam Sa'ad, Auwal; Khaliq, Ahmad; Saleh, Abdulmajid Obaid Hasan (IIUM Press, International Islamic University Malaysia, 2019)
Peer-to-peer financial services are increasingly becoming significant game changers in the financial sector across the globe. Initially, few structures were developed to help cater to the attention of the Islamic financial industry players involved in peer-to-peer dealings. The new trend of the technological evolution in the banking and financial sector has proved to be the next challenge in this sector. However, the survival of Islamic fintech will heavily rely on the existing established trust within the sector. The potential collaborations between the established Islamic banks, fintech players and start-ups will certainly unleash the potentials of today’s technologies in the Islamic finance industry. Being in their early stages, Malaysia and its counterparts from the GCC states have the potentials to becoming leaders in the Islamic fintech industry and may work together to develop a necessary framework for Islamic fintech advancement. Peer-to-peer arrangement connects crowdfunding investors with entrepreneurs through more transparency, speed dealings and almost free from complications in the documentation. In view of the fact that mushārakah is becoming more practical under the concept of Islamic peer-to-peer deals, this paper attempts to develop a new peer-to-peer financing which is underlain by the Mushārakah Smart Contract Model. The paper proposes a mushārakah model using Mushārakah Smart Contract in which the investors would be crediting their investments for mushārakah purposes with virtual lenders for specific Sharīʽah compliant businesses and share in the profit, based on an agreed dividend under the mushārakah principles. It also highlights the potential structures, cyber risks, and devices to mitigate them by using mushārakah standards and measures within the Sharīʽah principles.